A Note on the “Little Giant” Policy - Diego Lanzi (Journal of Management and Science, 2025)
In this note, we briefly address the “Little Giant” Policy both in theoretical and empirical terms. As our discussion shows, the farsightedness of the Chinese LGP has both empirical support and theoretical soundness. Surely, it is an example to imitate for countries having a large number of innovative small and medium-sized enterprises.